OzoNews Volume XVIII - 15-30 December 2018 - United Nations Environment Programme (2019)
In this issue: 1. Special End of Year Message, Tina Birmpili, Executive Secretary, Ozone Secretariat "The Kigali Amendment: A New Year’s resolution we cannot break". 2. Buildings and construction sector – Huge untapped potential for emission reductions. 3. Ozone depletion increases Antarctic snowfall, partially mitigates ice sheet loss. 4. How ice particles promote the formation of radicals. 5. Mini Screw: the development of a high-CFM compact compressor for LGWP A1 low-pressure refrigerant. 6. "The Dawn of a New Refrigeration Era - The Kigali Amendment for a Brighter Future". 7. OzonAction Brings Bangladesh Refrigeration and Air-Conditioning Professionals to China for Cool Training. 8. Centro Studi Galileo trains Chinese technicians on R290 A/C. 9. Japan to start helping Thailand collect greenhouse gas HCFCs next year. 10. Transforming the US market to phase down potent HFCs. 11. Washington governor proposes HFC-reduction program. 12. Centro Studi Galileo Certifies the first woman of the Middle East in RAC. 13. Turkmenistan greatly reduces use of ozone depleting substances.